Lecturers’ perspectives of teaching students with visual impairments: A case study of one TVET college in KwaZulu-Natal. - Msimango, Z. D.; Hlalele, D. J.; Subrayen, R. (South African Journal of Higher Education, 2026)
Inclusive education has become a critical aspect of the Higher Education system. This article explored ways to promote inclusivity and reduce exclusion in TVET colleges by addressing how lecturers view students with visual impairments. Drawing on the Learning Journey Theory (LJT) and Theory of Change (TOC), the researchers sought to re-conceptualise and understand lecturers’ learning journeys to facilitate inclusivity. Qualitative data was gathered from six TVET lecturers and analysed using thematic narrative analysis. The training of TVET lecturers to support students with VI emerged as a major barrier hindering the lecturers’ practice to enhance such students’ academic performance. Additional challenges included a dearth of educational resources, funding, inappropriate training programs, a lack of professional growth, and clear guidelines for educating visually impaired students. The findings indicate that policies for visually impaired students should be supported by thorough, ongoing training for lecturers. Furthermore, it is essential to have backing from government bodies and educational institutions to provide vital learning materials, assistive technologies, and well-defined policy guidelines. Hiring knowledgeable and empathetic instructors towards visually impaired students is another indispensable component.